Knowledge, attitudes and practices of patients and healthcare professionals regarding oral health and COPD in São Paulo, Brazil: a qualitative study - Matthew Riley (Nature Portfolio, 2021)
Abstract Poor oral health is associated with worse clinical outcomes in Chronic Obstructive Pulmonary Disease (COPD). This qualitative study aimed to investigate the knowledge, attitudes and practices of COPD patients and primary health care professionals (HCPs) in Brazil - where there are high rates of COPD and periodontal disease. Semi-structured interviews with COPD patients (n = 9) and three semi-structured focus groups with HCPs (n = 25) were conducted in São Paulo. Interviews were thematically analysed using The Framework Method. Despite a high prevalence of edentulism, patients viewed tooth loss and decay as a norm and neglected preventative oral health practices. HCPs blamed patients for avoiding preventative opportunities, whilst patients discussed significant barriers to oral healthcare. Knowledge of the relationship between oral health and COPD was lacking among HCPs and patients, but all participants were receptive to oral health education. Practitioners identified the need for a COPD primary care pathway that integrates oral health protocols. This study indicates that Brazil must incorporate preventative oral health into COPD management and expand public dental services to increase uptake.